Determination of the event collision time with the ALICE detector at the LHC - Adam, Jaroslav; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; Oeschler, Helmut; et al. (The European physical journal. Plus, 2017)
Particle identification is an important feature of the ALICE detector at the LHC. In particular, for particle identification via the time-of-flight technique, the precise determination of the event collision time represents an important ingredient of the quality of the measurement. In this paper, the different methods used for such a measurement in ALICE by means of the T0 and the TOF detectors are reviewed. Efficiencies, resolution and the improvement of the particle identification separation power of the methods used are presented for the different LHC colliding systems (pp, p-Pb and Pb-Pb) during the first period of data taking of LHC (RUN 1).
Gesehen am 18.06.2019
ALICE Collaboration: J. Adam, V. Anguelov, M. Arslandok, M.C. Danisch, A. Deisting, P. Glässel, J. Kim, S. Klewin, M.L. Knichel, L. Leardini, J. Mercado Pérez, H. Oeschler, A. Ohlson, Y. Pachmayer, F. Reidt, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, M.A. Völkl, D.F. Weiser, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und weitere]